EFFECTIVENESS OF CONVENTIONAL AND CORE STABILIZATION EXERCISES IN CONDITIONS WITH SPECIFC LOW BACK ACHE - Karanth, Vinith Vijaykumar; G. Varadharajulu, (International Journal of Psychosocial Rehabilitation, 2020)
This study was undertaken with the aim to determine the effectiveness of conventional and core stabilization exercises in conditions with specific low back ache. The basic objective of this study was to find out the effect of conventional exercises and core stabilization exercises in conditions with specific low back ache patients. This study was done in Krishna College of Physiotherapy, 36 patients who were diagnosed for Specific low back ache with age group between 35-60years were divided into two Groups A and B. 21 was males and 15 females in both the Groups. A thorough musculoskeletal assessment was performed and outcome was seen with Oswestry Low Back Pain Scale. First Group A was treated with Conventional exercises and Group B was treated with Core Stabilization exercises for 4 weeks. The pre and post intervention score was measured with Oswestry Low Back Pain Scale.Statistical analysis was done by using Instat software in which Wilcoxon Matched Pairs Test and Mann Whitney Test were used to analyze scores of Oswestry Low Back Pain Scale. Statistical analysis revealed that there was extremely significant difference between pre and post values of each Group A and B (P value=